1994
DOI: 10.1034/j.1600-0501.1994.050204.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant placement using a biodegradable barrier, polyhydroxybutyrate‐hydroxyvalerate reinforced with polyglactin 910. An experimental study in dogs.

Abstract: The purpose of this study was to evaluate the use of a biodegradable membrane of polyhydroxybutyrate-hydroxyvalerate copolymer reinforced with polyglactin 910 fibers, as an occlusive barrier over implants placed into fresh extraction sockets. Ten dogs had the 3rd and 4th mandibular premolars extracted bilaterally. Each dog had 4 Astra Dental Implants placed directly into the fresh extraction sockets. The top of the fixtures was placed at the same level as the top of the buccal cortical bone. The two implants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 0 publications
0
39
0
1
Order By: Relevance
“…Multi-centre studies have validated the predictability of placing implants at the time of extraction provided these procedures are appropriately treatment planned. PRACTICE 5,7,8,11,30,70,71 To date, evidence for placement of bone substitutes adjacent to small bone defects related to immediately placed implants appears safe, although these materials do not appear to predictably promote osseointegration. There is insufficient evidence that 'socket preservation' procedures predictably maintain socket anatomy without crestal resorption.…”
Section: Resultsmentioning
confidence: 99%
“…Multi-centre studies have validated the predictability of placing implants at the time of extraction provided these procedures are appropriately treatment planned. PRACTICE 5,7,8,11,30,70,71 To date, evidence for placement of bone substitutes adjacent to small bone defects related to immediately placed implants appears safe, although these materials do not appear to predictably promote osseointegration. There is insufficient evidence that 'socket preservation' procedures predictably maintain socket anatomy without crestal resorption.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the carboxy group in collagen is likely to form a chemical bond with calcium ion, and this bonding is thought to be involved in apatite crystal alignment. We also investigated an influence of Ca, PO 4 and collagen concentrations on the HAp/Col fiber growth and find that reducing these concentrations in the reaction vessel during synthesis allow to grow the fibers up to 75 mm as shown in Fig. 11.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, the regeneration of periodontal tissues was applied using a bioinert Teflon ® membrane or biodegradable collagen and polyester membranes. [1][2][3][4][5][6][7][8][9][10] These membranes were useful to regenerate periodontal tissues with a small bone defect less than 5 mm 3 in size, but were not applicable for a large bone defect because of their insufficient mechanical strength and low bone tissue affinity. Further, they still have connatural problems, i.e., Teflon ® needs operation for its excision, collagen has no mechanical strength even to handle it in operation and polyester sometimes induces serious inflammation with decreasing of surrounding pH by its degradation.…”
Section: Composite Membrane For Guided Bone Regenerationmentioning
confidence: 99%
“…(7)(8)(9)(10)(11) However, it has been reported that this rather complicated technique is not always successful. (12) This drawback argues for the alternative method with delayed titanium implant placement when membranes are used, as proposed by Buser et al ramic. (14,15) The purpose of the brittle HA implant is to maintain the bulk of the alveolar ridge by its physical presence for a limited time until a fixture can be placed.…”
mentioning
confidence: 99%